Investigating the fluid dynamics of rapid processes within microfluidic devices using bright-field microscopy1. Issue 9 (7th May 2015) - Pirbodaghi, Tohid; Vigolo, Daniele; Akbari, Samin; deMello, Andrew
<x xml:space="preserve">Abstract</x> To better understanding fluid dynamics within microfluidic channels, herein, we present an accurate experimental approach for studying the fluid dynamics of rapid processes within microfluidic devices using bright-field microscopy with white light illumination.